ANALISIS PERAN STAKEHOLDERS DALAM PENGEMBANGAN OBJEK WISATA MUSEUM DAN MONUMEN PALAGAN AMBARAWA DI KABUPATEN SEMARANG - Alma Rintawati, Rosita; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
This study aims to analyze the role of stakeholders and supporting and inhibiting factors in the development of the Ambarawa Palagan Museum and Monument tourist attraction. This research method is qualitative descriptive with data collection through in-depth interviews, observation, and documentation. The results of the study indicate that the roles of stakeholders involved include policy creators (Semarang Regent, Semarang Regency Tourism Office, Semarang Regency Regional Development Planning and Research Agency, and Semarang Regency Regional Finance Agency); coordinators (Semarang Regency Tourism Office, Regional Technical Implementation Unit for Tourism Objects, and Field Coordinators for tourism object management); facilitators (Semarang Regency Tourism Office, Public Works Office, Semarang Regency Environmental Office, Semarang Regency Transportation Office, and Central Java SCTv); implementers (Semarang Regency Tourism Office, Regional Technical Implementation Unit for Tourism Objects, and Field Coordinators for tourism object management); and accelerators (Semarang Regency Tourism Office, Semarang Regency Traditional Media Communication Forum, Raden Wijaya Wonogiri Buddhist College, Central Java SCTv, local communities and tourists). Then, the supporting factors consist of accessibility and determinants of stakeholder actions. Meanwhile, the inhibiting factors consist of stakeholder perceptions and participation. The conclusion of this study is that there are still challenges faced by stakeholders including suboptimal coordination between stakeholders, limited budget resources, lack of workforce and less attractive tourist attractions. Therefore, the researcher provides suggestions for improving communication and cooperation between stakeholders, increasing the number of workers and tourist attractions through the use of digital technology.